Análisis, desarrollo e implementación de un sistema web de auditoría y monitoreo medio ambiental para estaciones de comercialización de combustibles - Grijalva Calderón, Fabricio Edmundo (2016)
The present graduation work consists of the creation of an environmental audit web-based system for “Kuusa Soluciones Ambientales Environmental Consulting Company”. The scope of the project has been limited to environmental audits, exclusively designed for fuel dispensing stations located nationwide. Formerly, the company mentioned, developed environmental audits making use of basic tools such as Excel spreadsheets, and word processors. Therefore, a web based system becomes a practical solution for generating, monitoring, and control of documentation associated to environmental audit. The advantage and consequence of applying this system is the exceptional time saving, error plummeting, and the capacity of storing all information regarding the environmental audit and fuel dispensing stations, all in one repository. The system was developed using the Groovy programing language and PostgreSQL database manager as main tools; Scrum was used as the agile development methodology. The system´s main core is based in fulfilling all specific objectives that all fuel dispensing stations environmental audits should comply. The mentioned objectives are: evaluation of the condition of the different areas of the station, evaluation of the environmental condition, evaluation of the environmental applicable law, evaluation of the pre-approved environmental management plan, evaluation of the environmental license requisites, development of an action plan, development of an updated environmental management plan, and the generation of a yearly activity schedule based upon the updated environmental management plan. Each one of these objectives represent an internal module within the system, and in conjunction, all modules shape a fully developed environmental audit. The system is currently in a production state, and it´s being used by “Kuusa Soluciones Ambientales” staff.